Dakwah dan Politik - zumaroh zumaroh zumaroh (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2018)
Da'wah is the source of the existence of the Islamic religion. Islam requires every muslim to perform Da'wah, i.e. persuade to the kindness and prevent harm. Dawah would be effective if done in the right way. Dawah told to kindess and prevent harm the absence of both them have the distinguish consequence. Prevent evil Da'wah is full of risks and challenges. Therefore, preventing harm is not enough with advice but must be done with power or politics.